2004
DOI: 10.2209/tdcpublication.45.229
|View full text |Cite
|
Sign up to set email alerts
|

Canalicular Adenoma Arising in the Upper Lip: Review of the Pathological Findings

Abstract: This case report describes a rare case of canalicular adenoma arising in the upper lip of a 61-year-old male patient. Macroscopic examination of the tumor revealed a welldefined, smooth, firm, elastic hard, round nodule with a diameter of 1.0cm. The cut surface was white. Histopathology showed that the tumor was an encapsulated mass with a complex cellular pattern of anastomosing duct-like or trabecular structures lined by a single layer of tall columnar epithelial cells, which were embedded in a loose, fibrou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 16 publications
0
14
0
1
Order By: Relevance
“…The histologic differential diagnosis encompasses primarily salivary gland neoplasms, including basal cell adenoma, pleomorphic adenoma (PA), PLGA, adenoid cystic carcinoma (ACC), ductal adenoma, and reticulated myoepithelioma, while ameloblastoma, adenomatoid odontogenic tumor, paraganglioma, and skin basal cell carcinoma are also occasionally considered [16,21,25,32,88,107].…”
Section: Differential Diagnosismentioning
confidence: 99%
“…The histologic differential diagnosis encompasses primarily salivary gland neoplasms, including basal cell adenoma, pleomorphic adenoma (PA), PLGA, adenoid cystic carcinoma (ACC), ductal adenoma, and reticulated myoepithelioma, while ameloblastoma, adenomatoid odontogenic tumor, paraganglioma, and skin basal cell carcinoma are also occasionally considered [16,21,25,32,88,107].…”
Section: Differential Diagnosismentioning
confidence: 99%
“…These cells may be distributed in various arrangements as solid, trabecular, tubular and membranous [21]. In contrast, canalicular adenoma is char-DARIUSZ TYRALIK, ANETA DZIERWA-GAWRON, JANUSZ RYŚ acterized by a complex cellular pattern of anastomosing duct-like, trabecular or papillary-like structures lined by a single layer of tall columnar epithelial cells embedded in a loose, fibrous, and highly vascular connective tissue stroma [21][22][23]. What is more, the results of several immunohistochemical studies showed a distinct immunoprofile for both neoplasms [21].…”
Section: Discussionmentioning
confidence: 99%
“…The cells of the canalicular adenoma showed an immunohistochemical profile that indicates an excretory duct origin: most of these cells were immunoreactive to pancytokeratins (AE1/AE3), and S-100 protein, but were negative for smooth muscle actin (SMA), vimentin and CK13 or CK14 [23][24][25]. Rare focal staining with antiepithelial membrane antigen was also noted [25].…”
Section: Discussionmentioning
confidence: 99%
“…En la histopatología, se observan cordones de doble fila de células columnares o cúbicas con patrón alternante descrito como "collar de perlas" (beading): los cordones se disponen paralelamente en contacto estrecho y posteriormente se separan formando estructuras similares a ductos que dan origen al término "canalicular" de este tumor (1,3,4,(5)(6)(7)(8)(9)(11)(12)(13)(14). Estas estructuras similares a ductos, pueden dilatarse y llegar a conformar quistes con formaciones papilares (1,5,11).…”
Section: Hallazgos Morfológicosunclassified